Response of grain sorghum (Sorghum bicolor) cultivars to weed competition in semi-arid tropical India - MISHRA, J S; RAO, S S; PATIL, J V (The Indian Journal of Agricultural Sciences, 2015)
The performance of eleven grain sorghum [Sorghum bicolor (L.) Moench] cultivars on weed competition was evaluated in the semi-arid tropics of India during rainy seasons of 2009 and 2010 at Hyderabad. The experiment consisted of the three weeding levels (unweeded check, atrazine 0.50 kg/ha + hoeing once at 30 days after sowing- DAS, and atrazine + hoeing twice at 30 and 45 DAS) as the main plot treatments and eleven grain sorghum cultivars (CSH 16, CSH 23, CSH 14, SPH 1596, SPH 1606, SPH 1616, CSV 15, CSV 17, CSV 20, CSV 23, SPV 462) as the sub plots, was replicated thrice in a split-plot design. The cultivar competitiveness was associated with its ability to intercept solar radiation. Sorghum leaf area index (LAI) was negatively correlated (r = –0.82**) with a light transmission ratio (LTR) and weed dry weight at harvest (r = –0.81**). The yield reduction due to weed competition among cultivars varied from 21 to 53%. Grain yield was significantly and positively correlated with initial fresh shoot weight (r = 0.61*), LAI (r= 0.84**), panicle number (r = 0.68**), and significantly negatively correlated with weed biomass (r = –0.62*) and LTR (r = –0.77**). Sorghum hybrids CSH 16 resulted in better weed suppression, whereas CSH 14, SPH 1616 and SPH 1606 tolerated higher weed pressure. CSH 16 (unweeded and weeded once), and SPH 1596 (weeded twice) were the most profitable. Results showed that growing sorghum hybrid CSH 16 and controlling weeds with atrazine at 0.50 kg/ha as pre-emergence followed by 1 hoe weeding at 30 DAS would lead to higher yield and profits.